2020
DOI: 10.1002/mabi.201900342
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements in Using Polymers for Intestinal Mucoadhesion and Mucopenetration

Abstract: Oral administration of actives is the most desired form of delivery, but the formulations need to overcome a variety of barriers including the intestinal mucus. This feature article summarizes the developments from the past 2–3 years in this context focusing on polymer‐based formulations. The progress in assembling mucopenetrating nanoparticles is outlined considering coatings using noninteracting polymers as well as virus‐like particles and charge‐shifting particles. Next, polymers and their modification to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 89 publications
0
22
0
Order By: Relevance
“…260,261 The balance between the hydrophilic and hydrophobic nature of the nanoparticle interface and the digestive system is an important factor responsible for absorption into the body, and hydrophilic coating on the surface of hydrophobic nanoparticles has been widely accepted to increase their absorption. [297][298][299] Maisel et al prepared polystyrene nanoparticles coated with a hydrophilic polymer (PEG) and confirmed their localization to the small intestine in ex vivo studies in Figure 9 The digestive stages after oral administration and the mechanisms of in vivo uptake of surfactant-coated nanoparticles through the small intestine. International Journal of Nanomedicine downloaded from https://www.dovepress.com/ by 44.224.250.200 on 14-Jun-2021 For personal use only.…”
Section: Application Of Food Nanotechnology In the Digestive Systemmentioning
confidence: 86%
“…260,261 The balance between the hydrophilic and hydrophobic nature of the nanoparticle interface and the digestive system is an important factor responsible for absorption into the body, and hydrophilic coating on the surface of hydrophobic nanoparticles has been widely accepted to increase their absorption. [297][298][299] Maisel et al prepared polystyrene nanoparticles coated with a hydrophilic polymer (PEG) and confirmed their localization to the small intestine in ex vivo studies in Figure 9 The digestive stages after oral administration and the mechanisms of in vivo uptake of surfactant-coated nanoparticles through the small intestine. International Journal of Nanomedicine downloaded from https://www.dovepress.com/ by 44.224.250.200 on 14-Jun-2021 For personal use only.…”
Section: Application Of Food Nanotechnology In the Digestive Systemmentioning
confidence: 86%
“…The pharmaceutical industry must be evolving and improving processes for manufacturing accurate and repeatable intranasal dose in the coming years. In this review, we introduced the absorption mechanism, advantages including large absorption surface area, good patient compliance, rapid and high drug permeability, bypassing of hepatic first-pass metabolism, potential direct drug delivery to the brain along the olfactory nerves, and limitations, including rapid drug elimination prompted by mucociliary clearance (5 mm/min for healthy humans), limited administration volume (25-200 ml), and the presence of enzymes that degrade in nasal drug delivery route (Lechanteur et al, 2017(Lechanteur et al, , 2019Chen S. et al, 2020;Lechanteur and Evrard, 2020;Sabir et al, 2020;Taipaleenmaki and Stadler, 2020). Then, we systematically summarized the development of intranasal delivery carriers of antidepressants in clinical studies including nanogels, nanostructured lipid, liposomes nanoparticles, and nanoemulsions/microemulsion.…”
Section: Discussionmentioning
confidence: 99%
“…Muco-penetration particles are aimed to slip through the mucus with the modification of the particle surface, especially surface charge and viscosity [147]. Due to the overall negative charge of the mucus, formulations with noninteracting polymers, high-charge density net-neutral particles, charge-shifting particles are designed for better penetration of the mucus layer [148,149,154]. On the other hand, the mucoadhesive drug delivery system (MDDS) featuring a longer adhesion time and subsequent penetration through the epithelial membrane is also a desirable formulation design.…”
Section: The Importance Of Polymeric Excipients For Drug Permeability Enhancementmentioning
confidence: 99%